A turban effect, too: selection biases against women wearing Muslim headscarves - Unkelbach, Christian; Knäble, Helga; Gode, Kai; Senft, Miriam (Social psychological and personality science, 2010)
Traditional Muslim headscarves are called hijabs. The authors show that hijabs and headscarves are closely associated with people’s mental representation of “typical” Muslim women in Germany. They then investigate the influence of wearing such hijabs on acceptance rates in a human resources selection procedure. In this paradigm, the authors demonstrate a selection bias against women wearing hijabs: Although factual information about academic achievements had the largest effect on participants' decisions, decisions on all achievement levels were biased against women wearing hijabs. This pattern was substantiated by participants' response latencies; women wearing hijabs were more quickly rejected and more slowly accepted compared to women not wearing hijabs. The authors discuss these results' implications for public referendums (e.g., in Switzerland, 2009) and policy making (e.g., in France, 2004; in Germany, 2005) regarding Islamic culture.